The Routledge handbook of adoption - Wrobel, Gretchen Miller; Helder, Emily; Marr, Elisha (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Adoption is practiced globally yielding a multidimensional area of study that cannot be characterized by a single movement or discipline. The Handbook provides a central source of contemporary scholarship from a variety of disciplines with an international perspective and uses a multifaceted and interdisciplinary approach to ground adoption practices and activities in scientific research. Perspectives of birth/first parents, adoptive parents, and adopted persons are brought forth through a range of disciplinary and theoretical lenses. Beginning with background and context of adoption, including sociocultural and political contexts, the handbook then addresses the diversity of adoptive families in terms of family forms, attitudes about adoption, and characteristics of adopted children. Next, research examining the lived experience of adoption for birth parents, adoptive parents, and adopted individuals is presented. A variety of outcomes for internationally and domestically adopted children and adoptive families is then discussed and the Handbook concludes by addressing the development, training and implementation of adoption competent clinical practice. The primary purpose of this Handbook is to make scientific research easily accessible, comprehensible, and useful for the various stakeholders involved in adoption including members of the adoptive kinship network of birth and adoptive family members, the professionals who work with them, and those involved in adoption research and education"--
Communication about adoption -- Psychosocial development and adjustment -- Ethnic and cultural differences -- Searching and reconciliation with origins -- Practical implications and future lines of research -- Conclusions -- References -- 9. A critical adoption studies and Asian Americanist integrative perspective on the psychology of Korean adoption -- Adoption as natural experiment and intervention -- Adoption (and race) as a risk factor -- A critical adoption studies and Asian Americanist integrative approach to adoption studies -- The historical and cultural context of Korean adoption
OCLC-licensed vendor bibliographic record.
Keywords: Adoption; PSYCHOLOGY / Developmental / Adolescent; PSYCHOLOGY / Developmental / Child; PSYCHOLOGY / Developmental / General